The Challenges of Religious Literacy The Case of Finland - Sakaranaho, Tuula; Aarrevaara, Timo; Konttori, Johanna (SpringerBriefs in Religious Studies, 2020)
This open access book presents religious literacy as the main explanatory factor when dealing with certain ethnic groups that attract stereotypes which gloss over other personal factors such as age, class, gender and cultural differences. It discusses freedom of religion, and the Christian revival movement. It examines religious literacy and religious diversity in multi-faith schools. It looks into the role of Mosques and Islamic divorce. Finally, it discusses the prevention of violent radicalization and extremism in Finland. Using recent data on Finnish secular society, the book promotes a new understanding which is needed with respect to popular and media portrayal of religion, or with respect to public discussion about religion. It addresses actors in civic society, public servants and higher education.